Efektivitas Konseling Kelompok dengan Teknik Role Playing dalam Meningkatkan Self Control Pecandu Narkoba - Kusnadi; Aura Lutfia Putri; Hartika Utami Fitri (Sociocouns: Journal of Islamic Guidance and Counseling, 2026)
Self-control is an individual's ability to manage urges, emotions, and delay gratification in order to achieve long-term goals. Low self-control in drug addicts is one of the factors that increases the risk of relapse. The formulation of the problem in this study is how the picture of self-control of drug addicts before and after being given group counseling with role-playing techniques and how effective group counseling with role-playing techniques is in increasing self-control in drug addicts at YPRN Ar Rahman. This study aims to determine the picture of the level of self-control in drug addicts at YPRN Ar Rahman before and after being given group counseling with role-playing techniques and to determine the effectiveness of group counseling with role-playing techniques in increasing self-control in drug addicts at YPRN Ar Rahman. This research method uses a quantitative approach with a pre-experimental research type, namely one group pretest-posttest design. Based on the research results, the Wilcoxon test showed that with a value of 0.018 < 0.05, it can be concluded that Ha is accepted and Ho is rejected. These findings support Gottfredson and Hirschi's self-control theory and Bandura's social learning theory, that self-control can be improved through direct social experiences. Thus, group counseling using role-playing techniques has proven effective and can be an alternative psychological treatment in drug addict rehabilitation programs.